A Note on Intrinsic Inflation Persistence and the Optimal Inflation Rate - Pontiggia, Dario (Journal of Reviews on Global Economics, 2016)
This paper examines the implications of intrinsic inflation persistence, namely inertia that inflation inherits from its own past, on the conduct of optimal monetary policy. We study the optimal long-run rate of inflation in a basic New Keynesian model, which is augmented for intrinsic inflation persistence. We show that the commitment solution for the monetary authority leads to steady-state outcomes in which inflation is positive.